Geotechnical Analysis of Earth Dam Failure - Fathani, Teuku Faisal (2011)
Situ Gintung dam failure on 27 March 2009 has caused more than 100 casualties from a tsunami caused by more than 10 m/s flow velocity resulted from the embankment failure in only less than 2 hours. Prior to the dam failure, a relatively high intensity of rainfall (more than 70 mm/hrs) occurred at the catchment area. Besides, the embankment structural condition was far from fair. These were indicated by apparent physical conditions such as too narrow spillway, insufficient width of spillway crest, imperfect interface between spillway structure and soil embankment, utilization of downstream embankment for housing, road, etc. These, of course contributed the Situ Gintung dam failure phenomenon which needs to be studied thoroughly. The geotechnical analysis indicates that interaction between the dynamic of reservoir water level and the cutting slope of earth dam plays a significant role in the occurrence of dam failure. The appurtenances of Situ Gintung and the cutting slope due to the houses construction were evaluated to understand the historical aim of the dam development. A twodimensional stress-deformation analysis has been performed to figure out the distribution of relative shear stress and plastic points on the dam embankment at the time of failure. The safety factor decreases from 1.43 at the un-interfered embankment to 1.27 due to the cutting slope and the increase of reservoir water level.